-3pq+spr-7p-6=-6q-5

Simple and best practice solution for -3pq+spr-7p-6=-6q-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3pq+spr-7p-6=-6q-5 equation:


Simplifying
-3pq + spr + -7p + -6 = -6q + -5

Reorder the terms:
-6 + -7p + -3pq + prs = -6q + -5

Reorder the terms:
-6 + -7p + -3pq + prs = -5 + -6q

Solving
-6 + -7p + -3pq + prs = -5 + -6q

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + -7p + -3pq + 6 + prs = -5 + 6 + -6q

Reorder the terms:
-6 + 6 + -7p + -3pq + prs = -5 + 6 + -6q

Combine like terms: -6 + 6 = 0
0 + -7p + -3pq + prs = -5 + 6 + -6q
-7p + -3pq + prs = -5 + 6 + -6q

Combine like terms: -5 + 6 = 1
-7p + -3pq + prs = 1 + -6q

Reorder the terms:
-1 + -7p + -3pq + prs + 6q = 1 + -6q + -1 + 6q

Reorder the terms:
-1 + -7p + -3pq + prs + 6q = 1 + -1 + -6q + 6q

Combine like terms: 1 + -1 = 0
-1 + -7p + -3pq + prs + 6q = 0 + -6q + 6q
-1 + -7p + -3pq + prs + 6q = -6q + 6q

Combine like terms: -6q + 6q = 0
-1 + -7p + -3pq + prs + 6q = 0

The solution to this equation could not be determined.

See similar equations:

| 2a+(a+87)=180 | | .3333x=9 | | -7x-2(-7x+2)=38 | | 5d-d-2d+3d=0 | | x^2-15x+82=0 | | -2x+-3x=15 | | 2(r-3)=4(-3r-5) | | 7xy+0=7xy | | 2x^3-6x^2+6x-10=0 | | 17d-16d=14 | | 6(6)-33=d | | 3x^3-5x^2=0 | | 180-x-10=5(90-x) | | 180-x-10=3(90-x) | | 6a-12=30 | | 10x^2-x-42=0 | | 13x+13=11x+15 | | 2(x-7)+5x=153 | | 12x-23=49 | | 13y-3=23 | | 8x^3-64r^2+r-8=0 | | 14x+2=2+14x | | 2.6v=-28.6 | | 6(3)+1=c | | x+5=6x+49 | | 15r-7r=8 | | (8+x)x(10+x)=180 | | 3a^2+7a-20=0 | | t+9t=20 | | -(-6.9)=42.8 | | ab*3a=1564 | | S+5.3=3.2 |

Equations solver categories